2009
DOI: 10.1007/s00068-009-8068-6
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Fusion of an Unstable Atlantoaxial Fracture in a Completely Tetraplegic Patient Using Silicate-Substituted Calcium Phosphate

Abstract: Bone graft harvesting from the iliac crest constitutes the gold standard in spinal surgery due to its osteogenic, osteoconductive and osteoinductive properties. Large amounts of autograft can provoke complications like donor site morbidity, pain and the need for a second operation. Therefore, research into bone graft substitutes is of great interest. Silicate-substituted calcium phosphate (Actifuse(TM) Synthetic Bone Graft, ApaTech Ltd, London) was used in combination with morselized corticocancellous graft in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Kirschner et al 2 used Si-CaP for the treatment of benign bone defects in children, and confirmed its good therapeutic effect by clinical and radiological follow-up. Coincidentally, Putz et al 3 also used Si-CaP in the treatment of a transarticular stabilization (modified Magerl) of a completely tetraplegic patient with an unstable atlantoaxial fracture, and the follow-up results at 8 months showed that Si-CaP could be used as an alternative to iliac autograft in spinal surgery. In addition, Hutchens et al 4 implanted Si-CaP into a severe distal femoral defect model in sheep and observed excellent biocompatibility and bone healing in all experimental groups, which was consistent with the results of the above two clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Kirschner et al 2 used Si-CaP for the treatment of benign bone defects in children, and confirmed its good therapeutic effect by clinical and radiological follow-up. Coincidentally, Putz et al 3 also used Si-CaP in the treatment of a transarticular stabilization (modified Magerl) of a completely tetraplegic patient with an unstable atlantoaxial fracture, and the follow-up results at 8 months showed that Si-CaP could be used as an alternative to iliac autograft in spinal surgery. In addition, Hutchens et al 4 implanted Si-CaP into a severe distal femoral defect model in sheep and observed excellent biocompatibility and bone healing in all experimental groups, which was consistent with the results of the above two clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…143 Baxter Actifuse ® Flow has successfully been used for spinal fusion procedure. 144 When used in a comparative clinical study to the Medtronic Infuse ® graft, they were able to demonstrate similar fusion rates (Actifuse ® 9/9, Infuse ® 8/9 cases) and both products yielded similar alleviation of pain and improved quality of life. 145 Also, DBM solutions have been approved clinically for spinal application.…”
Section: Orthopedics: Trauma and Oncologymentioning
confidence: 96%
“…However, effective hydrogel therapies are emerging that do not depend on BMP‐based growth factors to obtain their therapeutic effect. The before mentioned Baxter Actifuse® Flow has successfully been used for spinal fusion procedure 144 . When used in a comparative clinical study to the Medtronic Infuse® graft, they were able to demonstrate similar fusion rates (Actifuse® 9/9, Infuse® 8/9 cases) and both products yielded similar alleviation of pain and improved quality of life 145 .…”
Section: Applicationsmentioning
confidence: 99%